3(4x-2)=2(9x+3)

Simple and best practice solution for 3(4x-2)=2(9x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4x-2)=2(9x+3) equation:



3(4x-2)=2(9x+3)
We move all terms to the left:
3(4x-2)-(2(9x+3))=0
We multiply parentheses
12x-(2(9x+3))-6=0
We calculate terms in parentheses: -(2(9x+3)), so:
2(9x+3)
We multiply parentheses
18x+6
Back to the equation:
-(18x+6)
We get rid of parentheses
12x-18x-6-6=0
We add all the numbers together, and all the variables
-6x-12=0
We move all terms containing x to the left, all other terms to the right
-6x=12
x=12/-6
x=-2

See similar equations:

| 6=4m+5-5m | | 6(-2-7x)=240 | | 35+13=x | | 9x-6+5x-10=180 | | 4x+3=-43 | | 35-13=x | | 16x-15-99=13 | | 60+20s=285 | | -5v+11=8 | | 7x-3(x-8=50(8x+2) | | 57=2(3+r) | | 3(5x−4)^2−25=2 | | 3b+11=5 | | 2x+6x–10=6 | | 2(16+w)=56 | | 10=4/5n-10 | | 2x+6x–10=6 | | 110y+10-11y=1 | | H(t)=-16t^2+40t+15 | | 2a-3=-5 | | 7x-3(x-8=1/2(8x+2) | | .4d+3.1=12.3 | | 8x-25=83 | | 0.04=25x | | (3x/10)+(4x/5)=11 | | –3s+8=4−2s | | 43=4.15/(.12-x) | | 27-3s=15 | | 8.33x=3.33x+40 | | -2x+3+5x=-9 | | -6-5(7b+5)=-171 | | -6x-6-2x=26 |

Equations solver categories